Shri Dhirubhai Ambani with Mrs. Kokila Ambani and Mukesh and Anil Ambani - Reliance Industries Limited (2022)
Shri Dhirubhai Ambani married Kokila Patel, daughter of Ratilal Patel of Jamnagar, Gujarat on March 12, 1955.